Some remarks on the significance of paradox for science in the context of photometric paradox case - Świeżyński, Adam (Studia Philosophiae Christianae, 2019)
A paradox is an argument that produces an inconsistency, typically within logic or common sense. Most paradoxes are known to be invalid arguments but are still valuable in promoting critical thinking. In astrophysics and physical cosmology, Olbers’ paradox (photometric; “dark night-sky”), named after German scholar Heinrich Olbers, is the argument that the darkness of the night sky conflicts with the assumption of an infinite and eternal static universe. If the universe is static and populated by an infinite number of stars, any sight line from Earth must end at the bright surface of a star, so the night sky should be completely bright. This contradicts the observed darkness of the night. Modern research on the essence of the photometric paradox (and attempts to neutralize it undertaken in the history of science) lead to the conclusion that its paradoxicality is resulting primarily from the precedence of human thought (ideas, theories) in relation to the possibility of its proper empirical verification. Therefore, the paradox of “dark night-sky” and attempts to overcome it may be instructive proof that something so plain and obvious, as available to anyone look at the starry night sky, sometimes, for respectively keen observer, give an opportunity to look ahead much further (and sometimes more accurately to reality) than empirical research allow at the moment. The photometric paradox created an opportunity for the unveiling of a new cognitive horizon by exceeding the existing scheme of thought and thereby acquiring new scientific knowledge, enriching the knowledge gained so far and deepening our understanding of Universe.